2022
DOI: 10.1021/acs.joc.2c00310
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Synthesis and Electrochemical and Photophysical Properties of 2,7-Diarylbenzo[1,2-d:4,3-d′]bis(thiazoles)

Abstract: This article focuses on the development of practical approaches to the preparation of benzo[1,2-d:4,3-d′]bis(thiazoles) using blue light-induced photochemical cyclization of N,N′-(1,4-aryl)dithioamides in the presence of p-chloranil as a mild oxidant. The proposed method allows to obtain benzo[1,2-d:4,3-d′]bis(thiazoles) containing donor substituents in the conjugated chain. Photophysical and (spectro)electrochemical properties of 2,6-di([2,2′-bithiophen]-5-yl)benzo[1,2-d:4,3-d′]bis(thiazole) and -benzo[1,2-d:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Obviously, such reaction conditions are not suitable for the synthesis of compounds containing thiophene and other easily oxidized donor substituents. It is known that sulfur-containing compounds are capable of photo-oxidative reactions. We have recently reported that benzobisthiazoles can be obtained by oxidative photocyclization . We studied the possibility of such an approach for the synthesis of compounds 6e and 7e .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Obviously, such reaction conditions are not suitable for the synthesis of compounds containing thiophene and other easily oxidized donor substituents. It is known that sulfur-containing compounds are capable of photo-oxidative reactions. We have recently reported that benzobisthiazoles can be obtained by oxidative photocyclization . We studied the possibility of such an approach for the synthesis of compounds 6e and 7e .…”
Section: Resultsmentioning
confidence: 99%
“…In the spectra of benzotriazole derivatives 7a – 7e , the low-frequency signals overlap each other (compounds 7a , 7b , 7d , and 7e ), and for compound 7c , they are recorded as one broadened signal. The absorption and emission spectra of dithiazolo[4′,5′:3.4;5″,4″:5.6]benzo[1,2-c][1,2,5]thiadiazoles 7a – 7e are similar to the spectra of previously obtained benzothiadiazoles but shifted to the long wavelength region. A bathochromic shift of absorption maxima is observed with an increase in the conjugation system of substituent R, as well as when passing from benzotriazole derivatives 7a – 7e to the corresponding benzothiadiazole derivatives 6a – 6e .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The arylation is powerful to convert benzobisthiazole 8 through two-fold arylation for the synthesis of 9 (Scheme 2B). This diarylation would be useful for the synthesis of new benzobisthiazole-based materials 12 for organic electronics. Chlorobenzothiazole 1b reacted with resorcinol ( 2j ) to yield the corresponding product 3bj , which underwent Cs 2 CO 3 -mediated S N Ar cyclization to yield tetracyclic aromatic system 10 (Scheme 2C).…”
mentioning
confidence: 99%